Repair and strengthening of concrete structures (FIP guide to good practice., 1991)
This 'Guide to Good Practice' focuses on the techniques for the repair and strengthening of reinforced and pre-stressed concrete structures - covering the planning, design, implementation and monitoring of repair and strengthening projects.